2003
DOI: 10.1590/s1415-43662003000200033
|View full text |Cite
|
Sign up to set email alerts
|

Consumo de combustível de um trator em função do tipo de pneu, da lastragem e da velocidade de trabalho

Abstract: Com o presente trabalho, teve-se como objetivo comparar o consumo de combustível de um trator agrícola operando com pneus (radial, diagonal e de baixa pressão) em duas condições de lastragem (com e sem água nos pneus) e quatro velocidades de deslocamento. O experimento foi realizado na FCAV-UNESP, Jaboticabal, SP, em condição de preparo do solo com escarificador. Utilizou-se um trator 4x2 TDA, com potência de 89 kW (121 CV) no motor. Os pneus foram do tipo R1, com as seguintes características: radial (dianteir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
10

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 1 publication
1
9
0
10
Order By: Relevance
“…The tractor in the same conditions, but with worn tires had a mean specific consumption of 651.84 g kWh -1 , showing an increase of 14.97% in specific fuel consumption in relation to the use of the tractor with metallic and water ballasts. This result is in agreement with those found by LOPES et al (2003). These authors concluded that the ballast with water (75% of the tire) offered to the tractor lower specific fuel consumption in comparison to the use of tires without water.…”
Section: -Coefficient Of Variationsupporting
confidence: 92%
See 2 more Smart Citations
“…The tractor in the same conditions, but with worn tires had a mean specific consumption of 651.84 g kWh -1 , showing an increase of 14.97% in specific fuel consumption in relation to the use of the tractor with metallic and water ballasts. This result is in agreement with those found by LOPES et al (2003). These authors concluded that the ballast with water (75% of the tire) offered to the tractor lower specific fuel consumption in comparison to the use of tires without water.…”
Section: -Coefficient Of Variationsupporting
confidence: 92%
“…This technical form can be used to compare engines, tractors and equipments of different sizes and shapes (LOPES et al, 2003). In Table 6, it can be observed that, at different levels of inflation pressure used in new tires, the tractor does not present variation of specific fuel consumption, as opposed to the use of worn tires, which showed variation for all indexes, where fuel consumption was lower, the higher the inflation pressure.…”
Section: -Coefficient Of Variationmentioning
confidence: 99%
See 1 more Smart Citation
“…The specific fuel consumption and the required power (17) determine the hourly fuel consumption (L h -1 ) (23), which related to the field capacity, provides the operational consumption (L ha -1 ) (26). One must emphasize that fuel consumption may vary due to the tractor features such as tire type, weight and work speed (Lopes et al, 2003).…”
Section:  mentioning
confidence: 99%
“…Average power on traction bar was determined indirectly, using equation (1) For fuel consumption measuring, a prototype was used, as described by LOPES et al (2003). For volumetric consumption determination, eq.…”
Section: Experiments Was Installed In the Machinesmentioning
confidence: 99%